2018
DOI: 10.1038/s41598-018-31923-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vaspin on Insulin Resistance in Rats and Underlying Mechanisms

Abstract: Insulin resistance (IR) is the main pathogenesis of metabolic syndrome and a shared pathophysiological change in conditions such as diabetes mellitus, adiposity, hypertension, and atherosclerosis. Visceral adipose tissue-derived serpin (Vaspin) is a newly discovered adipocytokine with insulin-sensitizing and anti-inflammatory effects. To examine if vaspin can improve insulin resistance in rats fed a high-fat diet via the insulin receptor substrate/phosphatidylinositol 3 kinase/protein kinase B/glucose transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…Sakamoto et al [31] examined the effects of vaspin (1μg/kg/day, 14 days, n = 4) treatment on MCT-induced rise in pulmonary arterial hypertension (PA) pressure and RV to body weight ratio (RV/BW), and demonstrated that vaspin significantly attenuate the rise in PA pressure but have no effect on the body weight. While Liu et al [32] showed that a downward trend in body weight could be seen in HFD-fed rats treated with vaspin (320 ng/kg/day, intraperitoneally, n = 10) for 8 weeks except for significantly decreasing fasting blood glucose and fasting insulin concentrations. However, in this study, no statistically significant.in food intake could be seen in rats treated with vaspin.…”
Section: Discussionmentioning
confidence: 94%
“…Sakamoto et al [31] examined the effects of vaspin (1μg/kg/day, 14 days, n = 4) treatment on MCT-induced rise in pulmonary arterial hypertension (PA) pressure and RV to body weight ratio (RV/BW), and demonstrated that vaspin significantly attenuate the rise in PA pressure but have no effect on the body weight. While Liu et al [32] showed that a downward trend in body weight could be seen in HFD-fed rats treated with vaspin (320 ng/kg/day, intraperitoneally, n = 10) for 8 weeks except for significantly decreasing fasting blood glucose and fasting insulin concentrations. However, in this study, no statistically significant.in food intake could be seen in rats treated with vaspin.…”
Section: Discussionmentioning
confidence: 94%
“…Vaspin-mediated activation of PI3K/AKT has been reported previously in several other cell types, including pancreatic cells (Liu et al 2017), 3T3-L1 preadipocytes (Liu et al 2015) and endothelial progenitor cells . Furthermore, it was recently reported that vaspin promotes the PI3K/AKT signalling pathway leading to increased GLUT4 protein expression in rats fed a high-fat diet (Liu et al 2018) and can improve glucose tolerance in mice . Therefore, our demonstration that vaspin induces activation of PI3K-AKT signalling and increases insulin sensitivity in obese human myotubes is significant.…”
Section: Discussionmentioning
confidence: 99%
“…VASPIN inhibits KALLIKREIN 7 by a classical serpin mechanism with high specificity and may thereby contribute to improved insulin sensitivity (Heiker et al, , reviewed in Heiker, ). A second potential pathway was described by Jung et al, who propose a model in which VASPIN acts via the PI3 kinase/AKT pathway and ameliorates atherosclerosis (Jung et al, ; Liu et al, ). This finding was further supported by the analysis of Nicholson et al , showing an induction of the PI3 kinase/AKT axis by VASPIN and thereby promoting GLUT4 expression and translocation (Nicholson et al, ).…”
Section: Introductionmentioning
confidence: 99%